EFEKTIVITAS INQUIRY BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA: ANALISIS BERDASARKAN SELF REGULATED LEARNING - Mulia, Rawit Suci; Hasibuan, Ismail Mulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the effect of the Inquiry-Based Learning model on students' mathematical communication skills of self-regulated learning. The study employed a quantitative approach using an experimental method with a factorial design. The sample was selected through cluster random sampling, where Class VII.A served as the experimental group and Class VII.B as the control group. Data were collected through tests, questionnaires, observations, and documentation. The research instruments consisted of a mathematical communication skills test, a self-regulated learning questionnaire, and observation sheets. Data were analyzed using a two-way ANOVA test. The results showed that: (1) there was a significant difference in mathematical communication skills between students taught using the Inquiry-Based Learning model and those taught using the direct instruction model; (2) there was a significant difference in mathematical communication skills among students with high, moderate, and low levels of self-regulated learning; and (3) there was no interaction effect between the Inquiry-Based Learning model and self-regulated learning on students' mathematical communication skills. In conclusion, both the Inquiry-Based Learning model and self-regulated learning significantly influence students' mathematical communication skills independently, but no significant interaction effect was found between the two factors.